2019
DOI: 10.1002/jlb.mr0318-095rr
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage heterogeneity and plasticity in tuberculosis

Abstract: Macrophages are the primary host cells for Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), during its intracellular survival in humans. The pathogen has a remarkable capacity to survive within the hostile environment of macrophages. However, primary infection does not result in active TB disease in most individuals. The majority of individuals remain latently infected, wherein the bacteria are held in check by the host immune response. Nevertheless, such individuals can develop active TB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 69 publications
(152 reference statements)
1
81
0
5
Order By: Relevance
“…M1 polarization primes macrophages for a variety of pro-inflammatory cell-mediated responses, among them granuloma formation. M2 polarization, meanwhile, accompanies humoral immunity, is favored by IL-10 stimulation, and redirects uninfected MDMs from granuloma formation to wound repair [65]. GLCCs formed under conditions favoring M2 polarization more closely model activation of latent Map than they do the early stages of latency, while the latter is what we aim to simulate.…”
Section: Discussionmentioning
confidence: 99%
“…M1 polarization primes macrophages for a variety of pro-inflammatory cell-mediated responses, among them granuloma formation. M2 polarization, meanwhile, accompanies humoral immunity, is favored by IL-10 stimulation, and redirects uninfected MDMs from granuloma formation to wound repair [65]. GLCCs formed under conditions favoring M2 polarization more closely model activation of latent Map than they do the early stages of latency, while the latter is what we aim to simulate.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are crucial players of the inflammatory response triggered by tissue damage and exhibit remarkable phenotypic plasticity (51,54). Live tracking of fluorescently labeled macrophages in zebrafish showed that these cells are recruited to injury shortly after neutrophils at early stages [several papers].…”
Section: Cxcr3 and Ccr2 Axes In Wound-induced Inflammationmentioning
confidence: 99%
“…The M.tb infection is regulated by both immune and pathogenic factors [15,16]. The research on the body immunity mainly focuses on the regulation of various cytokines on tuberculous granulomas and the function and type of T cells in the development of tuberculous granulomas.…”
Section: Discussionmentioning
confidence: 99%